Severe growth retardation and distinctive phenotype in a child with 1q24 deletion syndrome (BIRDEM Medical Journal, 2025)
Microdeletions on the long arm of chromosome 1 are relatively uncommon. In recent years, a consistent phenotype has emerged in association with 1q24q25 deletions. These patients have mild to moderate intellectual disability and characteristic skeletal features including small hands and feet with brachydactyly, prenatal onset growth retardation and persisting significant postnatal short stature of up to -5SD with microcephaly up to - 4SD. The reported dysmorphic facial features include micrognathia, small, low set ears, a short nose with a broad bridge and bulbous tip, full eye lids, a tented upper lip and a small chin. Other features less frequently described include renal, cardiac and genital malformations, craniosynostosis, hypotonia and seizures. We report a rare, microarray-confirmed case of 1q24 deletion syndrome presenting with classic phenotypic features. The patient, a three-year-old female, presented with failure to thrive, developmental delay including intellectual disability and motor delay. She has characteristic facial and skeletal features, as well as multiple congenital anomalies. The diagnosis was confirmed by genetic analysis during the evaluation process. Supportive management was initiated, and available informations were shared with the parents about course and probable prognosis. BIRDEM Med J 2025; 15(3): 146-149